Outcomes of percutaneous coronary intervention in COVID-19-positive acute coronary syndrome patients: a retrospective study in Vietnam - Duy Cao Phuong Le; Duy Cao Phuong Le; Nguyet Thi Minh Nguyen; Quan Duy Vo; Quan Duy Vo (Frontiers in Cardiovascular Medicine)
BackgroundCoronavirus disease 2019 (COVID-19) has disrupted the management of acute coronary syndrome (ACS), with emerging evidence suggesting increased complications and mortality among patients undergoing percutaneous coronary intervention (PCI). However, data from low- and middle-income settings such as Vietnam remain limited. This study aimed to evaluate the clinical characteristics and outcomes of ACS patients with COVID-19 undergoing PCI at a tertiary hospital in Vietnam.MethodsThis retrospective cohort study was conducted at a tertiary hospital in Ho Chi Minh City from 2019 to 2022. Adult patients diagnosed with ACS who underwent PCI were included and stratified by COVID-19 status confirmed via RT-PCR. All patients received standard guideline-directed therapy, including dual antiplatelet and anticoagulant regimens, and were followed for 1 year to assess clinical outcomes.ResultA total of 118 patients were included, comprising 26 COVID-19-positive and 92 COVID-19-negative individuals. Baseline characteristics and cardiovascular risk factors were generally comparable between the two groups. While procedural success rates were similar, COVID-19-positive patients demonstrated higher thrombus burden and significantly increased rates of ICU admission, prolonged hospitalization, and MACCE at all timepoints. COVID-19 severity, cardiogenic shock, and multivessel disease emerged as independent predictors of adverse outcomes.ConclusionIn this Vietnamese cohort, COVID-19 infection was associated with worse clinical outcomes following PCI for ACS. These findings highlight the need for early risk stratification and resource planning during pandemic conditions. However, the small sample size, single-center design, and observational nature of the study limit its generalizability, and causal inferences should be drawn with caution.